2009
DOI: 10.1194/jlr.r800030-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

GPIHBP1, a GPI-anchored protein required for the lipolytic processing of triglyceride-rich lipoproteins

Abstract: GPIHBP1, a small glycosylphosphatidylinositolanchored glycoprotein, is required for the lipolytic processing of triglyceride-rich lipoproteins. GPIHBP1 knockout mice exhibit chylomicronemia, even on a low-fat diet, with plasma triglyceride levels of 3,500-5,000 mg/dl. GPIHBP1 is expressed highly in heart, adipose tissue, and skeletal muscle, the same tissues that express high levels of lipoprotein lipase (LPL). In each of these tissues, GPIHBP1 is located in capillary endothelial cells. Chinese hamster ovary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Direct evaluation of this hypothesis is complicated because Lpl Ϫ / Ϫ mice die shortly after birth. Sonnenburg et al ( 48 ) found that genetic ablation or antibody-mediated inactivation of ANGPTL3 decreased plasma TG levels by 26% in fed mice lacking GPIHBP1, a protein required for the transport of LPL to the capillary endothelial surface ( 49 ). Unfortunately, those authors did not report plasma levels of cholesterol for this experiment.…”
Section: Inactivation Of Angptl3 Does Not Affect Fatty Acid Uptake Bymentioning
confidence: 57%
“…Direct evaluation of this hypothesis is complicated because Lpl Ϫ / Ϫ mice die shortly after birth. Sonnenburg et al ( 48 ) found that genetic ablation or antibody-mediated inactivation of ANGPTL3 decreased plasma TG levels by 26% in fed mice lacking GPIHBP1, a protein required for the transport of LPL to the capillary endothelial surface ( 49 ). Unfortunately, those authors did not report plasma levels of cholesterol for this experiment.…”
Section: Inactivation Of Angptl3 Does Not Affect Fatty Acid Uptake Bymentioning
confidence: 57%
“…The similarity of the N-terminal acidic sequence of PCSK9 to that of GPIHBP1, which enhances lipase hydrolysis of triglycerides in chylomicrons (31)(32)(33), led us to show that these domains could be swapped without a deleterious effect on the PCSK9 function (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we noted a significant similarity in acidity and length of the Tyr 38 -sulfated, Ser 47 -phosphorylated aa 31-58, 31 QEDEDGDYEELV-LALRSEEDGLAEAPEH 58 , of PCSK9 to the heparin-like, Tyr-sulfated, acidic stretch, including aa 24 -51, 24 QEEEEED-EDHGPDDYDEEDEDEVEEEET 51 , at the N terminus of the glycosylphosphatidylinositol-anchored protein GPIHBP1. The latter domain binds lipoprotein lipase and apolipoprotein AV on chylomicrons, thereby enhancing lipoprotein lipase activity on triglycerides (31)(32)(33). Note that 13/14 acidic residues of PCSK9 (including the Tyr sulfation and Ser phosphorylation sites) align with similar residues in human GPIHBP1 (Fig.…”
Section: Effect Of Prosegment On the Pcsk9-induced Ldlrmentioning
confidence: 99%
“…Gpihbp1 is expressed primarily in capillaries of heart, adipose tissue, and skeletal muscle, where it localizes to the luminal surface of endothelial cells ( 151,152 ). Gpihbp1 probably directs fat toward energy sinks, such as the heart and adipose tissue ( 153 ). Gpihbp1 is regulated by PPAR ␥ , with increased expression during fasting and return to baseline after refeeding ( 154 ).…”
Section: Phospholipid Transfer Proteinmentioning
confidence: 99%